1983
DOI: 10.1002/ana.410130303
|View full text |Cite
|
Sign up to set email alerts
|

Central pontine myelinolysis following rapid correction of hyponatremia

Abstract: Central pontine and extrapontine myelinolysis was experimentally produced in dogs by the rapid correction of severe, sustained, vasopressin-induced hyponatremia. Hyponatremia alone or slowly corrected hyponatremia did not produce the disease. Affected dogs showed rigid quadriparesis. The central pons, lateral aspects of the thalamus and adjacent internal capsules, deep layers of cerebral cortex and subjacent white matter, cerebellum, and other regions were symmetrically involved. Myelin and oligodendroglia wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0
11

Year Published

1986
1986
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(81 citation statements)
references
References 29 publications
2
67
0
11
Order By: Relevance
“…With the exception of glycine, amino acids and their derivatives are highest in the cerebrum and cerebellum, I) \ (9) and plasma osmolality (29). The concentrations of glycine in the brainstem decrease significantly with hyponatremia and increase after rapid correction of the hyponatremia, thus, they play a major role on the osmoregulation in the brainstem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of glycine, amino acids and their derivatives are highest in the cerebrum and cerebellum, I) \ (9) and plasma osmolality (29). The concentrations of glycine in the brainstem decrease significantly with hyponatremia and increase after rapid correction of the hyponatremia, thus, they play a major role on the osmoregulation in the brainstem.…”
Section: Resultsmentioning
confidence: 99%
“…Sterns et al (5) reported that neurological complications occur more frequently in hyponatremic patients with a higher correction rate of serum sodium. In experimental animals, including rats (6,7), rabbits (8), and dogs (9), rapid correction of hyponatremia has been shown persistently resulting in demyelinative lesions. However, not all investigators agree on the association of rapid correction of hyponatremia with CPM.…”
mentioning
confidence: 99%
“…*P < 0.05 compared to slow correction rate development of neurological complications after liver transplantation is more closely associated with the correction rate of hyponatremia rather than hyponatremia. The risks of rapid correction of hyponatremia itself and its associations with osmotic demyelination syndrome have been demonstrated in animal models (Kleinschmidt-DeMasters and Norenberg 1981;Laureno 1983;Verbalis and Martinez 1991), and the risk of rapid correction is currently emphasized in clinical practice. Rapid correction rate was associated with neurological sequelae in patients with severe hyponatremia (Sterns et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and experimental observations have suggested that rapid correction of severe chronic hyponatremia (serum Na < 120 meq/liter) is associated with the development of central pontine myelinolysis (13)(14)(15)(16)(17)(18). Verbalis and Drutarosky have demonstrated that chronic hyponatremia induced by the combination of minipump infusion of DDAVP and feeding of a liquid diet is well tolerated by rats (20).…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have definitively shown that symmetrical demyelinating lesions of the central nervous system occur after hypertonic infusion for correction of severe chronic hyponatremia (15)(16)(17)(18). Slow correction of hyponatremia, however, does not appear to be associated with this neurological lesion either clinically or experimentally (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%